2009
DOI: 10.1021/am900296h
|View full text |Cite
|
Sign up to set email alerts
|

Improved Morphology and Performance from Surface Treatments of Naphthalenetetracarboxylic Diimide Bottom Contact Field-Effect Transistors

Abstract: We report bottom contact organic field-effect transistors (OFETs) with various surface treatments based on n-channel materials, specifically, 1,4,5,8-naphthalene-teracarboxylic diimides (NTCDIs) with three different fluorinated N-substituents, systematically studied with a particular emphasis on the interplay between the morphology of the organic semiconductor films and the electrical device properties. The morphological origins of the improvements were directly and dramatically visualized at the semiconductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Compound 1h with perfluorophenyl substituents showed a low mobility of 0.025 cm 2 V −1 s −1 with bottom gate (BG) bottom contact (BC) geometry. However, much higher mobility of 0.87 cm 2 V −1 s −1 was obtained using bottom gate top contact (TC) geometry 57. Another work reported a mobility of 0.31 cm 2 V −1 s −1 when measured in ambient air using the same OSCs of 1h 58…”
Section: N‐type Semiconductors For Ofetsmentioning
confidence: 99%
“…Compound 1h with perfluorophenyl substituents showed a low mobility of 0.025 cm 2 V −1 s −1 with bottom gate (BG) bottom contact (BC) geometry. However, much higher mobility of 0.87 cm 2 V −1 s −1 was obtained using bottom gate top contact (TC) geometry 57. Another work reported a mobility of 0.31 cm 2 V −1 s −1 when measured in ambient air using the same OSCs of 1h 58…”
Section: N‐type Semiconductors For Ofetsmentioning
confidence: 99%
“…After 100 days in air, the average mobility of three OTFTs decreased from 0.62 to 0.12 cm 2 V −1 s −1 , but stabilized thereafter. In addition, the NDI derivatives with fluorinated phenyl groups or phenyl groupsubstituted fluorinated alkyls chain, 240i and 240j afforded the highest electron mobilities of 0.57 and 0.87 cm 2 V −1 s −1 , respectively [301,302]. The chlorinesubstituted NDIs 241a and 241b, which were reported by Oh et al, showed excellent electron mobilities of 0.86 and 1.26 cm 2 V −1 s −1 in nitrogen, respectively [298].…”
Section: Diimidesmentioning
confidence: 72%
“…Air‐stable n‐type TFTs with mobility values as high as 0.57 cm 2 V −1 s −1 have been demonstrated by Kevin See et al for NTCDI derivatives with multiple –F and –CF 3 substituted aliphatic/benzylic amines 30. Single or multiple CF 3 groups on a small side chain such as benzyl greatly increased air stability31–35 Sun et al reported that using aromatic thiols to modify the Au electrodes could improve morphology and performance of the NTCDI bottom‐contact TFTs 36…”
Section: Transparent and Printable Organic And Polymer Electronicsmentioning
confidence: 99%